Enhancing Engagement and Comprehension Through Joyful Learning in Qur'an and Hadith Education - Saiful Lutfi; Sardimi Sardimi; Siti Norhidayah (STAI Syaichona Moh. Cholil Bangkalan, 2026)
This study explores the implementation of the joyful learning model to improve the quality of Qur’an and Hadith instruction at MAN Kotawaringin Timur, a senior Islamic high school in Central Kalimantan, Indonesia. A mixed-methods design was employed, combining qualitative approaches—classroom observation, semi-structured interviews, and documentation analysis—with quantitative student surveys and formative assessments. The findings reveal that joyful learning effectively increased student engagement and motivation. More than 90% of students agreed that game-based and collaborative activities made it easier to understand the material, while teachers observed higher participation and enthusiasm throughout the lessons. The average formative test score reached 84 out of 100, reflecting solid comprehension and active involvement. These results indicate that joyful learning fosters a dynamic, participatory, and meaningful classroom atmosphere that supports deeper understanding of Qur’an and Hadith lessons. The study concludes that joyful learning is a promising pedagogical approach for enhancing engagement, motivation, and learning outcomes in Islamic religious education at the Madrasah Aliyah level.